Lithium ion battery composite packaging film and lithium ion battery
By using a composite metal foil layer composed of a reinforced metal layer and a corrosion-resistant metal layer in lithium-ion batteries, combined with the design of the thermoplastic resin layer, the problem of insufficient strength of the composite aluminum-plastic film is solved, and the mechanical strength and ductility of the battery are improved. Enhanced battery safety and energy density.
Patent Information
- Application Number
- CN202420032114.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2034-01-05
AI Technical Summary
The strength of the existing composite aluminum-plastic film is relatively low, which limits the use of silicon-based negative electrodes and the increase in the energy density of lithium-ion batteries, especially during the expansion of high silicon negative electrodes, which can easily lead to the destruction of the battery cell packaging material.
The composite metal foil layer composed of a reinforced metal layer and a corrosion-resistant metal layer, combined with a thermoplastic resin layer, is used to form a composite packaging film of lithium-ion battery, which increases mechanical strength and ductility and is suitable for high-voltage positive electrode and high-silicon negative electrode chemical system.
It improves the packaging safety and service life of lithium-ion batteries, and at the same time enhances the ability to improve battery energy density.
Smart Images

Figure CN222338378U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of composite packaging film materials, in particular to a lithium ion battery composite packaging film and a lithium ion battery. Background Art
[0002] In recent years, due to the rise of the electronic consumer products industry, people have a great demand for lithium-ion batteries. Soft-pack batteries have good safety and great advantages in lightness, thinness, special shape, flexible design, high volume energy density, etc., so they occupy a large market share in the consumer electronics, automobile, military, medical, power tools and other industries.
[0003] Soft-pack batteries generally use composite aluminum-plastic film as packaging material. Composite aluminum-plastic film has extremely high barrier properties, good cold stamping formability and puncture resistance, electrolyte stability, high temperature resistance, and strong insulation. Therefore, aluminum-plastic composite film is the most commonly used in the soft-pack battery market.
[0004] In recent years, due to the demand for improving the energy density of lithium-ion batteries, more and more lithium-ion batteries have added higher and higher content of silicon materials in the negative electrode materials to improve the energy density of the battery cells. However, the silicon-based negative electrode will expand greatly during the charging and cycling process. Due to the low strength of the composite aluminum-plastic film, the expansion of the high-content silicon-based negative electrode will directly lead to an increase in the thickness of the battery cell and even the destruction of the battery cell packaging material. Therefore, the soft-pack battery using the composite aluminum-plastic film in the prior art greatly limits the use of silicon-based negative electrodes and the continuous improvement of the volume energy density of the battery cell. Utility Model Content
[0005] Aiming at the problem of low strength of the existing battery packaging composite aluminum-plastic film, the utility model provides a lithium ion battery composite packaging film and a lithium ion battery.
[0006] On the one hand, the utility model provides a lithium-ion battery composite packaging film, which includes a composite metal foil layer and a thermoplastic resin layer from the outside to the inside, wherein the composite metal foil layer includes a reinforcing metal layer and a corrosion-resistant metal layer, and the corrosion-resistant metal layer is arranged on both sides of the reinforcing metal layer, or the corrosion-resistant metal layer is arranged on the side of the reinforcing metal layer facing the thermoplastic resin layer.
[0007] Optionally, the thickness of the composite metal foil layer is 10-100 μm, the thickness of the reinforcing metal layer is 10-80 μm, and the thickness of the corrosion-resistant metal layer is 0.1-20 μm.
[0008] Optionally, the reinforced metal layer includes one or more of a stainless steel layer, a titanium alloy layer, an Al-Zn-Mg-Cu alloy layer, a magnesium alloy layer, a nano-twinned steel layer, a high entropy alloy layer, an Inconel 718 alloy layer, a nano-bainite steel layer, a nano-structured molybdenum alloy layer, a dual-phase alloy layer, a eutectic high entropy alloy layer and a low-density steel layer.
[0009] Optionally, the tensile strength of the reinforced metal layer is greater than 300 MPa, and the elongation is greater than 10%.
[0010] Optionally, the corrosion-resistant metal layer includes one or more of an aluminum foil layer, an aluminum alloy layer, a titanium foil layer and a titanium alloy layer.
[0011] Optionally, a heat-resistant resin layer is provided on the side of the composite metal foil layer facing away from the thermoplastic resin layer, and the heat-resistant resin layer is connected to the composite metal foil layer by providing a first adhesive layer.
[0012] Optionally, an ink layer is provided between the heat-resistant resin layer and the first adhesive layer; and a matte layer is provided on a side of the heat-resistant resin layer away from the ink layer.
[0013] Optionally, the corrosion-resistant metal layer is connected to the thermoplastic resin layer by providing a second adhesive layer.
[0014] Optionally, the first adhesive layer is provided between the reinforcing metal layer and the corrosion-resistant metal layer.
[0015] On the other hand, the utility model further provides a lithium ion battery, comprising any one of the lithium ion battery composite packaging films described above.
[0016] In the utility model, by providing a reinforcing metal layer and a corrosion-resistant metal layer, the lithium-ion battery composite packaging film not only has the characteristics of low thickness and light weight, but also takes into account mechanical strength and ductility, meets the packaging requirements of the battery cell, can enhance the safety of soft-pack lithium batteries, and increase their service life. At the same time, it is suitable for lithium-ion batteries using high-voltage positive electrodes and high-silicon negative electrode chemical systems, which is conducive to the continuous improvement of the energy density of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a schematic structural diagram of a lithium-ion battery composite packaging film provided by an embodiment of the utility model;
[0018] Figure 2 It is a structural schematic diagram of a lithium-ion battery composite packaging film provided by another embodiment of the utility model;
[0019] Figure 3 This is a schematic structural diagram of a lithium-ion battery composite packaging film provided by another embodiment of the utility model;
[0020] Figure 4 This is a schematic structural diagram of a lithium-ion battery composite packaging film provided by another embodiment of the utility model;
[0021] Figure 5 This is a schematic structural diagram of a lithium-ion battery composite packaging film provided by another embodiment of the utility model;
[0022] Figure 6 It is a structural schematic diagram of a lithium-ion battery composite packaging film provided by another embodiment of the utility model.
[0023] The reference numerals in the drawings of the specification are as follows:
[0024] 1. Composite metal foil layer; 11. Strengthening metal layer; 12. Corrosion-resistant metal layer;
[0025] 2. Thermoplastic resin layer;
[0026] 3. Heat-resistant resin layer;
[0027] 4. First bonding layer;
[0028] 5. Ink layer;
[0029] 6. Matt layer;
[0030] 7. Second adhesive layer. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the utility model more clear, the utility model is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described here are only used to explain the utility model and are not used to limit the utility model.
[0032] In order to illustrate the technical solution of the present utility model, specific embodiments are provided below for illustration.
[0033] On the one hand, if Figure 1-Figure 6 As shown, a lithium-ion battery composite packaging film according to an embodiment of the utility model comprises a composite metal foil layer 1 and a thermoplastic resin layer 2 from outside to inside, the composite metal foil layer 1 comprises a reinforcing metal layer 11 and a corrosion-resistant metal layer 12, the corrosion-resistant metal layer 12 is arranged on both sides of the reinforcing metal layer 11, or the corrosion-resistant metal layer 12 is arranged on the side of the reinforcing metal layer 11 facing the thermoplastic resin layer 2. Specifically, the thermoplastic resin layer 2 can be bonded to one side of the corrosion-resistant metal layer 12 by an adhesive, or the corrosion-resistant metal layer 12 can be directly evaporated on the thermoplastic resin layer 2.
[0034] In the embodiment of the utility model, by providing the reinforcing metal layer 11 and the corrosion-resistant metal layer 12, the lithium-ion battery composite packaging film not only has the characteristics of low thickness and light weight, but also takes into account the mechanical strength and ductility, meets the packaging requirements of the battery cell, can enhance the safety of the soft-pack lithium battery, and increase its service life. At the same time, it is suitable for lithium-ion batteries using high-voltage positive electrode and high-silicon negative electrode chemical systems, which is conducive to the continuous improvement of the energy density of lithium-ion batteries.
[0035] The thermoplastic resin layer 2 is used to encapsulate the battery cell and needs to have excellent chemical resistance such as not peeling off when immersed in electrolyte, and resistance to electrolyte immersion and corrosion and trace hydrofluoric acid corrosion. In one embodiment, the thermoplastic resin layer 2 is selected from one or more of polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins.
[0036] The polyolefin includes one or more of polyethylene, homopolypropylene, block copolymer of polypropylene, random copolymer of polypropylene, terpolymer of ethylene-butene-propylene. The polyolefin is preferably polyethylene or polypropylene. Polyethylene includes one or more of low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene. Block copolymer of polypropylene includes block copolymer of propylene and ethylene. Random copolymer of polypropylene includes random copolymer of propylene and ethylene.
[0037] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, wherein the olefin includes one or more of ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. The cyclic monomer includes one or more of norbornene, cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene.
[0038] The acid-modified polyolefin refers to a polymer obtained by block polymerization or graft polymerization of the above polyolefin using an acid component such as carboxylic acid. The acid component used for modification includes one or more of maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.
[0039] The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or an anhydride thereof, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or anhydride thereof with the cyclic polyolefin.
[0040] The thermoplastic resin component is preferably one of unstretched films of polypropylene, maleic acid-modified polypropylene, ethylene acrylate copolymer, and ionomer resin.
[0041] The thermoplastic resin layer 2 may be formed of only one layer, or may be formed of two or more layers using the same or different resin components.
[0042] The thickness of the thermoplastic resin layer 2 is not particularly limited. To reduce the thickness and ensure processability, heat sealing properties, etc., the thickness is 10-100 μm, preferably 10-60 μm.
[0043] In some embodiments of the present invention, the thickness of the composite metal foil layer 1 is 10-100 μm, the thickness of the reinforcing metal layer 11 is 10-80 μm, and the thickness of the corrosion-resistant metal layer 12 is 0.1-20 μm.
[0044] In a preferred embodiment, the thickness of the reinforcing metal layer 11 is 20-50 μm, and the thickness of the corrosion-resistant metal layer 12 is 1-5 μm.
[0045] In one embodiment of the utility model, the reinforcing metal layer 11 is a metal or alloy material with high mechanical strength and high ductility, so as to increase the mechanical strength of the composite metal foil layer 1 while retaining its ductility. Specifically, the reinforcing metal layer 11 includes one or more of a stainless steel layer, a titanium alloy layer, an Al-Zn-Mg-Cu alloy layer, a magnesium alloy layer, a nano twin steel layer, a high entropy alloy layer, an Inconel 718 alloy layer, a nano bainite steel layer, a nano structured molybdenum alloy layer, a dual phase alloy layer, a eutectic high entropy alloy layer and a low density steel layer.
[0046] In a preferred embodiment, the reinforcing metal layer 11 is a high-strength and high-toughness stainless steel layer.
[0047] In some embodiments of the present invention, the tensile strength of the reinforced metal layer 11 is greater than 300 MPa, and the elongation is greater than 10%.
[0048] In a preferred embodiment, the tensile strength of the reinforced metal layer 11 is greater than 500 MPa, and the elongation is greater than 15%.
[0049] In a preferred embodiment, the tensile strength of the reinforced metal layer 11 is greater than 600 MPa, and the elongation is greater than 20%.
[0050] In some embodiments of the present invention, the corrosion-resistant metal layer 12 is a lightweight metal or alloy material that is highly ductile, resistant to electrolyte and hydrofluoric acid corrosion, and non-corrosive at high positive electrode potentials. Specifically, the corrosion-resistant metal layer 12 includes one or more of an aluminum foil layer, an aluminum alloy layer, a titanium foil layer, and a titanium alloy layer.
[0051] In a preferred embodiment, the corrosion-resistant metal layer 12 is an aluminum foil layer.
[0052] like Figure 1-Figure 3As shown, in some embodiments of the present invention, a heat-resistant resin layer 3 is provided on the side of the composite metal foil layer 1 facing away from the thermoplastic resin layer 2 , and the heat-resistant resin layer 3 is connected to the composite metal foil layer 1 by providing a first adhesive layer 4 .
[0053] The heat-resistant resin layer 3 mainly plays the role of appearance beautification, protection and information printing. The material of the heat-resistant resin layer 3 includes but is not limited to polyester resin, polyamide resin, epoxy resin, acrylic resin, fluororesin, polyurethane resin, silicone resin, phenolic resin and their mixtures, copolymers and other resin films.
[0054] The material of the heat-resistant resin layer 3 is preferably polyester resin and polyamide resin, more preferably biaxially stretched polyester resin and biaxially stretched polyamide resin. The polyester resin film is selected from one or more of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, copolyester, and polycarbonate. The polyamide resin includes one or more of nylon 6, nylon 66, a copolymer of nylon 6 and nylon 66, and polymethoxy adipamide (MXD6).
[0055] The first adhesive layer 4 can bond the heat-resistant resin layer 3 and the reinforcing metal layer 11 / corrosion-resistant metal layer 12. The adhesive used to form the first adhesive layer 4 can be a two-component curing adhesive or a single-component curing adhesive. There is no particular limitation on the bonding mechanism of the adhesive used to form the first adhesive layer 4, and it can be any one of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressing type, etc.
[0056] The adhesive forming the first adhesive layer 4 includes, but is not limited to, one or more of polyester resins, polyether adhesives, polyurethane adhesives, epoxy resins, phenolic resins, polyamide resins, polyolefin resins, polyvinyl acetate resins, cellulose adhesives, (meth)acrylic resins, polyimide resins, amino resins, rubber, and silicone resins.
[0057] The polyester resin includes one or more of ethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, polycarbonate, and copolymer polyester.
[0058] The polyamide resin includes one or more of nylon 6, nylon 66, nylon 12, and copolymer polyamide.
[0059] The polyolefin resin includes one or more of polyolefin, carboxylic acid-modified polyolefin, and metal-modified polyolefin. The amino resin includes one or more of urea resin and melamine resin.
[0060] The rubber includes one or more of chloroprene rubber, nitrile rubber, and styrene-butadiene rubber.
[0061] Preferably, the adhesive forming the first adhesive layer 4 is a polyurethane adhesive.
[0062] In one embodiment, the thickness of the heat-resistant resin layer 3 is 10 to 30 μm. There is no particular limitation on the thickness of the first adhesive layer 4, as long as it can play an adhesive function to ensure the bonding force between the heat-resistant resin layer 3 and the composite metal foil layer 1. For the purpose of reducing the thickness and weight of the packaging material, the thickness of the first adhesive layer 4 is preferably 1 to 5 μm.
[0063] like Figure 3 As shown, in some embodiments of the present invention, an ink layer 5 is provided between the heat-resistant resin layer 3 and the first adhesive layer 4. A matte layer 6 is provided on the side of the heat-resistant resin layer 3 away from the ink layer 5. The ink layer 5 and the matte layer are provided to improve the appearance of the composite packaging film and facilitate printing.
[0064] like Figure 1-5 As shown, in some embodiments of the utility model, the corrosion-resistant metal layer 12 is connected to the thermoplastic resin layer 2 by providing a second adhesive layer 7. The second adhesive layer 7 is a layer provided to firmly bond the corrosion-resistant metal layer 12 to the thermoplastic resin layer 2. The second adhesive layer 7 is formed by an adhesive capable of bonding the corrosion-resistant metal layer 12 to the thermoplastic resin layer 2. The bonding mechanism, adhesive composition and type of the adhesive used are similar to those of the adhesive forming the first adhesive layer 4. The adhesive used in the second adhesive layer 7 is preferably a polyolefin resin, more preferably a carboxylic acid-modified polyolefin resin, and particularly preferably a carboxylic acid-modified polypropylene.
[0065] In a preferred embodiment, the thickness of the second adhesive layer 7 is preferably 1-5 μm.
[0066] like Figure 5 and Figure 6 As shown, in some embodiments of the present invention, the first bonding layer 4 is provided between the reinforcing metal layer 11 and the corrosion-resistant metal layer 12 .
[0067] by Figure 1-Figure 3 Taking the structure of the lithium-ion battery composite packaging film shown in the figure as an example, the preparation method thereof comprises the following steps:
[0068] The reinforcing metal layer 11 is pretreated, and the pretreatment includes alkali washing, acid washing, water washing and drying.
[0069] The corrosion-resistant metal layer 12 is vacuum-deposited on one or both sides of the reinforcing metal layer 11, or magnetron sputtering, hot-dip plating, or vacuum-deposited after magnetron sputtering is performed on one or both sides of the reinforcing metal layer 11, or the corrosion-resistant metal layer 12 is composited by hot pressing through the first adhesive layer 4.
[0070] The thermoplastic resin layer 2 is subjected to low-temperature plasma treatment.
[0071] A polyolefin resin adhesive is roll-coated on the inner surface of the prepared composite metal foil layer 1 to form a second adhesive layer 7, and the thermoplastic resin layer 2 is dry-laminated and compounded on the surface of the second adhesive layer 7.
[0072] The heat-resistant resin layer 3 is subjected to low-temperature plasma treatment.
[0073] A polyurethane resin adhesive is roll-coated on the outer surface of the composite metal foil layer 1 to form a first adhesive layer 4, and the heat-resistant resin layer 3 is dry-laminated and composited on the surface of the first adhesive layer 4.
[0074] The composite packaging film for lithium ion batteries is obtained by aging and heating at 50 to 100° C. for 2 to 6 days.
[0075] or, comprising the following steps:
[0076] The reinforcing metal layer 11 is pretreated, and the pretreatment includes alkali washing, acid washing, water washing and drying.
[0077] The corrosion-resistant metal layer 12 is vacuum-deposited on one or both sides of the reinforcing metal layer 11, or magnetron sputtering, hot-dip plating, or vacuum-deposited after magnetron sputtering is performed on one or both sides of the reinforcing metal layer 11, or the corrosion-resistant metal layer 12 is composited by hot pressing through the first adhesive layer 4.
[0078] The thermoplastic resin layer 2 is subjected to corona treatment.
[0079] A corrosion-resistant metal layer 12 is vacuum-deposited on one side of the corona-treated thermoplastic resin film.
[0080] The surface of the reinforcing metal layer 11 is roughened, cleaned and / or plasma treated to increase surface adhesion.
[0081] An adhesive for forming the first adhesive layer 4 is applied to one side of the surface-treated reinforcing metal layer 11 .
[0082] The thermoplastic resin film with the corrosion-resistant metal layer 12 is laminated and composited with the first adhesive layer 4 side of the reinforcing metal layer 11 with the first adhesive layer 4 .
[0083] The heat-resistant resin layer 3 is subjected to a corona treatment.
[0084] Ink and adhesive are applied to one side of the treated heat-resistant resin layer 3 , and a matte layer 6 is applied to the other side. The adhesive is the adhesive that forms the first adhesive layer 4 .
[0085] The adhesive side of the obtained heat-resistant resin layer 3 and the roughened side of the reinforcing metal layer 11 are laminated and composited.
[0086] The composite packaging film for lithium ion batteries is obtained by aging and heating at 50 to 100° C. for 2 to 6 days.
[0087] On the other hand, an embodiment of the present invention further provides a lithium-ion battery, comprising any one of the lithium-ion battery composite packaging films described above.
[0088] The present invention is further described below by way of embodiments.
[0089] Example 1
[0090] A composite packaging film for lithium-ion batteries comprises, from outside to inside, a 20-μm stainless steel foil layer, a 3-μm first adhesive layer, a 1-μm aluminum layer, and a 25-μm cast polypropylene film, with a total thickness of 49 μm.
[0091] The specific preparation steps are as follows:
[0092] Take a 25μm cast polypropylene film roll CPP, perform corona treatment on the film surface to make its surface tension reach 38-42 dyne / cm, place the roll film in a vacuum chamber, close the vacuum chamber and evacuate. When the vacuum degree reaches a certain level (4×10 -4 mba or above), the evaporation boat is heated to 1300℃~1400℃, and then the aluminum wire with a purity of 99.9% is continuously fed to the evaporation boat. The unwinding speed, winding speed, wire feeding speed and evaporation amount are adjusted, and the cooling source is turned on to make the aluminum wire melt and evaporate continuously on the evaporation boat, so that a bright aluminum layer is formed on the surface of the moving film after cooling to obtain an aluminum-plated film.
[0093] A 20 μm thick stainless steel foil is subjected to alkaline washing, water washing, acid washing, water washing, and drying to obtain a clean stainless steel foil layer. Then, a 3 μm polyolefin resin adhesive is roller-coated on the inner surface of the stainless steel foil layer.
[0094] The aluminum layer of the aluminized film is facing the polyolefin resin adhesive, and the film is dry-laminated and thermally compounded on the surface of the adhesive layer at a thermal compounding temperature of 120-180°C. Finally, the obtained composite packaging film is placed at 60°C for aging and heating for 3 days and 80°C for aging and heating for 2 days to form a lithium-ion battery composite packaging film.
[0095] Example 2
[0096] A composite packaging film for lithium-ion batteries, which includes, from outside to inside, a 3μm matte layer 6, a 6μm PET layer, a 3μm black ink and a first adhesive layer, a 20μm stainless steel foil layer, a 1μm aluminum layer, a 3μm second adhesive layer and a 25μm cast polypropylene film, with a total thickness of 61μm.
[0097] The specific preparation steps are as follows:
[0098] The stainless steel foil with a thickness of 20 μm was subjected to alkaline washing, water washing, acid washing, water washing, and drying to obtain a clean stainless steel foil layer. The surface was subjected to corona treatment to make its surface tension reach 38-42 dyne / cm. The rolled stainless steel foil was placed in a vacuum chamber, and the vacuum chamber was closed and evacuated. When the vacuum degree reached a certain level (4×10 -4 mba or above), the evaporation boat is heated to 1300℃~1400℃, and then the aluminum wire with a purity of 99.9% is continuously fed to the evaporation boat. The unwinding speed, winding speed, wire feeding speed and evaporation amount are adjusted, and the cooling source is turned on to make the aluminum wire melt and evaporate continuously on the evaporation boat, so that a bright aluminum layer is formed on the surface of the moving stainless steel foil after cooling, and the aluminum-plated stainless steel composite foil is obtained.
[0099] On the surface of the aluminum-plated layer of the aluminum-plated stainless steel composite foil, a 3μm polyolefin resin adhesive is micro-concave coated.
[0100] A 25 μm thick cast polypropylene film coil is hot-pressed and bonded to an aluminum-plated stainless steel composite foil coated with an adhesive at a hot-pressing temperature of 120-180° C. to obtain an aluminum-plated stainless steel foil with a heat-sealing layer.
[0101] A 6 μm thick PET film roll was taken, one side was matte treated, and the other side was coated with a 3 μm adhesive layer with black ink to obtain an outer protective film.
[0102] The adhesive layer of the outer protective film is directed toward the stainless steel surface of the aluminum-plated stainless steel foil with the hot air layer for hot pressing and compounding at a temperature of 100-120° C. to obtain an aluminum-plated stainless steel foil with an inner heat sealing layer and an outer protective layer.
[0103] The obtained multilayer composite film was placed at 60° C. for 3 days and at 80° C. for 2 days to form a lithium-ion battery composite packaging film.
[0104] The above embodiments are only used to illustrate the technical solutions of the utility model, rather than to limit them. Although the utility model is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the utility model, and should be included in the protection scope of the utility model.
Claims
1. A lithium-ion battery composite packaging film, characterized in that: From outside to inside, it includes a composite metal foil layer and a thermoplastic resin layer, the composite metal foil layer includes a reinforcing metal layer and a corrosion-resistant metal layer, the corrosion-resistant metal layer is arranged on both sides of the reinforcing metal layer, or the corrosion-resistant metal layer is arranged on the side of the reinforcing metal layer facing the thermoplastic resin layer.
2. The lithium-ion battery composite packaging film according to claim 1, characterized in that: The thickness of the composite metal foil layer is 10-100 μm, the thickness of the reinforcing metal layer is 10-80 μm, and the thickness of the corrosion-resistant metal layer is 0.1-20 μm.
3. The lithium-ion battery composite packaging film according to claim 1, characterized in that: The reinforcing metal layer is selected from one of a stainless steel layer, a titanium alloy layer, an Al-Zn-Mg-Cu alloy layer, a magnesium alloy layer, a nano-twin steel layer, a high entropy alloy layer, an Inconel718 alloy layer, a nano-bainite steel layer, a nano-structured molybdenum alloy layer, a dual-phase alloy layer, a eutectic high entropy alloy layer and a low-density steel layer.
4. The lithium-ion battery composite packaging film according to claim 3, characterized in that: The tensile strength of the reinforced metal layer is greater than 300Mpa, and the elongation is greater than 10%.
5. The lithium-ion battery composite packaging film according to claim 1, characterized in that: The corrosion-resistant metal layer is selected from one of an aluminum foil layer, an aluminum alloy layer, a titanium foil layer and a titanium alloy layer.
6. The lithium-ion battery composite packaging film according to claim 1, characterized in that: A heat-resistant resin layer is arranged on the side of the composite metal foil layer away from the thermoplastic resin layer, and the heat-resistant resin layer is connected to the composite metal foil layer by arranging a first adhesive layer.
7. The lithium-ion battery composite packaging film according to claim 6, characterized in that: An ink layer is arranged between the heat-resistant resin layer and the first adhesive layer; and a matte layer is arranged on a side of the heat-resistant resin layer away from the ink layer.
8. The lithium-ion battery composite packaging film according to claim 1, characterized in that: The corrosion-resistant metal layer is connected to the thermoplastic resin layer by providing a second adhesive layer.
9. The lithium-ion battery composite packaging film according to claim 1, characterized in that: A first adhesive layer is provided between the reinforcing metal layer and the corrosion-resistant metal layer.
10. A lithium ion battery, characterized in that: The invention comprises the lithium ion battery composite packaging film according to any one of claims 1 to 9.